Viability of Cardboard Splints in the Emergency Management of Lower Limb Fractures - Wahome, R.; Harborne, D.; Ellis, R. (Medical Research Archives, 2024)
At Mbarara Regional Referral Hospital Uganda, 60% of all admissions are due to severe trauma, 30-35% of which are from tibia/fibular fractures. Emergency splinting of these fractures can be lifesaving and ideally, Plaster of Paris (P.O.P) is the gold standard. Improvised cardboard splints have replaced P.O.P, since they were more readily available and thought to be less expensive to apply especially during the covid 19 pandemic supply chain crisis. While anecdotal evidence exists dating since the First World War, scarce published works exist in measuring the clinical effectiveness of cardboard splints in comparison to P.O.P. The aim of this study was to find out if cardboard can be an effective and cheaper emergency alternative splint to P.O.P especially during the supply chain crises frequent in low resource environments. A prospective, experimental, cadaveric study was done where 44 open tibia-fibular fractures were splinted with both cardboard and P.O.P. The clinical effectiveness of cardboard and P.O.P splints was found through the measurement of immobilization at a fracture site via the use of 5 angular and 9 linear measurements. Cost comparisons of the splint were also done. Cardboard proved to be the non-inferior splint in 9 of the 14 measures of effectiveness. In the other 4 measures, no statistically significant differences were seen, while P.O.P was superior in 1 measurement. Cardboard proved to be the least expensive splint. During extreme shortages, cardboard could be considered as an emergency material for adequate splinting of lower limb fractures.
Keywords: Cardboard splints; Emergency management; Lower limb fractures; Tibia fractures; Fibula fractures; Plaster of Paris (P.O.P); Trauma care; Low-resource environments